2019
DOI: 10.1101/846154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual kinetochore-fibers locally dissipate force to maintain robust mammalian spindle structure

Abstract: At cell division, the mammalian kinetochore binds many spindle microtubules that make up the kinetochore-fiber. To segregate chromosomes, the kinetochore-fiber must be dynamic and generate and respond to force. Yet, how it remodels under force remains poorly understood. Kinetochore-fibers cannot be reconstituted in vitro, and exerting controlled forces in vivo remains challenging. Here, we use microneedles to pull on mammalian kinetochore-fibers and probe how sustained force regulates their dynamics and struct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Thus, MT-flux might regulate the fine balance between MCAK-dependent depolymerization and CLASPs-promoting polymerization of k-fibers to ensure the steady-state length of the mitotic spindle. Interestingly, a recent elegant study used microneedlebased mechanical manipulation to pull on photomarked k-fibers and showed that the applied pulling force on KTs suppressed depolymerization of k-fibers, resulting in their elongation via MT plus-end polymerization (Long et al, 2020). Likewise, the sliding activities of four MT-flux driving motors might exert similar forces on KTs to promote MT plus-end polymerization.…”
Section: Microtubule Fluxmentioning
confidence: 99%
“…Thus, MT-flux might regulate the fine balance between MCAK-dependent depolymerization and CLASPs-promoting polymerization of k-fibers to ensure the steady-state length of the mitotic spindle. Interestingly, a recent elegant study used microneedlebased mechanical manipulation to pull on photomarked k-fibers and showed that the applied pulling force on KTs suppressed depolymerization of k-fibers, resulting in their elongation via MT plus-end polymerization (Long et al, 2020). Likewise, the sliding activities of four MT-flux driving motors might exert similar forces on KTs to promote MT plus-end polymerization.…”
Section: Microtubule Fluxmentioning
confidence: 99%
“…Furthermore, evidence also suggests that lateral cross-links along the length of the k-fiber help to reinforce the k-fiber and alter its mechanical properties. K-fiber bundles appear to be much straighter and stiffer than individual microtubules (Goshima et al, 2005) and rupture collectively when subjected to sufficient force (Long et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…K-fiber bundles appear to be much straighter and stiffer than individual microtubules ( Goshima et al. , 2005 ) and rupture collectively when subjected to sufficient force ( Long et al. , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This drop, together with the action of the phosphatase PPP2CA, causes NuMA's phosphorylation state to drop. This precipitates the translocation of significant amounts of NuMA from spindle poles and the spindle to the cortex, where it, together with bound dynein, drives spindle elongation during anaphase [66][67][68][69][70]. Given all this, one would predict that in the absence of Myo10-dependent WEE1 sequestration (i.e.…”
Section: Discussionmentioning
confidence: 99%